2018
DOI: 10.1016/j.jastp.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Nonkinematic solar dynamo models with double-cell meridional circulation

Abstract: Employing the standard solar interior model as input we construct a dynamically-consistent nonlinear dynamo model that takes into account the detailed description of the Λ-effect, turbulent pumping, magnetic helicity balance, and magnetic feedback on the differential rotation and meridional circulation. The background mean-field hydrodynamic model of the solar convection zone accounts the solar-like angular velocity profile and the double-cell meridional circulation. We investigate an impact of the nonlinear m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 77 publications
(154 reference statements)
2
12
0
Order By: Relevance
“…The equatorial drift of the toroidal magnetic field in the subsurface shear layer, i.e. above 0.9R, is provided by the Parker-Yoshimura law (Yoshimura 1975) and the latitudinal turbulent pumping; see the detailed discussion of these effects in Pipin (2018). Similar mechanisms are also suggested by direct numerical simulations, e.g.…”
Section: Dynamo Modelsupporting
confidence: 53%
See 1 more Smart Citation
“…The equatorial drift of the toroidal magnetic field in the subsurface shear layer, i.e. above 0.9R, is provided by the Parker-Yoshimura law (Yoshimura 1975) and the latitudinal turbulent pumping; see the detailed discussion of these effects in Pipin (2018). Similar mechanisms are also suggested by direct numerical simulations, e.g.…”
Section: Dynamo Modelsupporting
confidence: 53%
“…In this paper we will discuss the kinematic version of the mean-field dynamo model developed recently by Pipin (2018) and . We study the mean-field induction equation in a turbulent perfectly conducting medium…”
Section: Dynamo Modelmentioning
confidence: 99%
“…The non-axisymmetrical flows (which reflects the North-South asymmetry of magnetic field) obtained from local helioseismology data showed that the symmetrical component is dominant (Kosovichev & Zhao 2016). The asymmetry can be explained by fluctuations of the dynamo α-effect (Pipin 2018). Apparently, the zonal flows of Cycle 24 at high latitudes are substantially weaker than the flows of Cycle 23, and this corresponds to the weaker magnetic activity in Cycle 24 (Howe et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Details of this process are still unclear. Recent results of direct numerical simulations (Warnecke et al 2018) and the non-kinematic dynamo model (Pipin 2018) suggest that the diffusive dynamo wave migration proceeds with the help of turbulent pumping. The emerging toroidal magnetic field forms active regions.…”
Section: Discussion: Solar Dynamo Scenariomentioning
confidence: 99%
“…are given in Pipin (2018). Their radial profiles depend on the mean density stratification, profile of the convective RMS velocity uc and on the Coriolis number Ω * = 2Ω0τc, where the Ω0 is the angular velocity of the star and τc is the convective turnover time.…”
Section: Dynamo Modelmentioning
confidence: 99%